2022
DOI: 10.1021/acs.jpclett.2c02098
|View full text |Cite
|
Sign up to set email alerts
|

“Magic” Molecules and a New Look at Chemical Diversity of Hydrocarbons

Abstract: We address the question why among the multitude of imaginable C n H m compositions some are easily synthesizable and abundant in nature, while others are not. To shed light on this problem we borrow approaches from nanocluster study, where stability with respect to neighboring compositions is used as a criterion of “magic” (particularly stable) clusters. By merging this criterion with predictions of lowest-energy structures of all C n H m molecules in a wide range of compositions (n ≤ 20, m ≤ 42) we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The present simulations at finite temperature extend the very recent survey of stable hydrocarbon structures at zero temperature (Ref. 38), and emphasize the key role of entropy in medium size clusters. However, kinetic considerations were ignored and we expect the observation time scale to play an important role on the possible characterization of the various species identified in the phase diagrams.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The present simulations at finite temperature extend the very recent survey of stable hydrocarbon structures at zero temperature (Ref. 38), and emphasize the key role of entropy in medium size clusters. However, kinetic considerations were ignored and we expect the observation time scale to play an important role on the possible characterization of the various species identified in the phase diagrams.…”
Section: Discussionsupporting
confidence: 85%
“…2-4,24 Quite a number of theoretical studies using different potential energy surfaces have focused on low-energy structures, typically explored as a function of the number of carbon and hydrogen atoms. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] While a) Present address: Department of Physical Chemistry, University of Geneva, 30 Quai Ernest-Ansermet, 1211 Geneva 4, Switzerland b) Electronic mail: cyril.falvo@universite-paris-saclay.fr these studies generally highlighted the dependence of the results on the specific energy model, they all concluded that for small pure carbon clusters (N C 8) the lowest isomers are linear chains, followed by rings (8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RF from large PAHs with low-lying electronic states could also contribute to the near-IR continuum emission, and its correlation to AIBs would be worth investigating further. Considering that PAHs are stabilised over cages due to a few extra hydrogen atoms (Perez-Mellor et al 2022;Lepeshkin et al 2022), applying the present statistical framework to those compounds would appear to be a natural extension of this work. In Dubosq et al (2020), the electronic oscillator strength of all S n → S 0 transitions were determined using the timedependent DFTB approach.…”
Section: Discussionmentioning
confidence: 99%
“…The method was successfully used for the global optimization of various systems. [42][43][44][45] Next, after the inspection of the evolutionary global optimization results, we performed an additional structure search. It consisted in identifying structural fragments, frequently appearing in the USPEX search, and connecting them in all possible ways, as described in Section 3.…”
Section: Methodsmentioning
confidence: 99%